REEL RHYTHMS: A STUDY ON HOW CARNATIC MUSICIANS EMBRACE INSTAGRAM'S REEL ROUTE TO RESONATE WITH THE YOUNGER GENERATION - Venkatraman, Srivaralaxmi; P, Uma Maheswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Carnatic Music, a symbol of our culture and tradition is performed in cultural festivals and events across the country with Chennai being the Locus for it. With the advent of new age technology and social media platforms, musicians have started using them to connect and communicate with general audience. Before Covid-19 pandemic, reels and short videos were not frequent. However, during and after the lockdown, Instagram, Youtube and Facebook have become the primary platform for Carnatic musicians to exhibit and engage. We also observe a huge number of followers-fan base for musicians like Sanjay Subramaniam, Aurna Sairam, Rajhesh Vaidhya, Abby V, Sudha Raghunathan, Mahesh Raghavan across social media platforms. Young musicians and artists struggling to break through the music ascendency in society find Instagram and Facebook as valuable platforms in reaching out to common people. The research focuses on why Carnatic musicians have started using Instagram extensively and the ways adopted to interact with the audience. This study examines the use of Instagram by 10 popular Carnatic musicians, analysing their social media engagement parameters. The research has referred to the Uses and Gratification theory to categorise the requirements of using this medium of communication. The study includes in-depth interviews with budding musicians to understand their perspective on engaging in Instagram promotions and gratifications they get. The analysis and results reveal the gradual increase of musicians using Instagram and other social media platforms without compromising the art form.